(x^2+3x+2)(x^2+7x+12)+1
=(x2+x+2x+2)(x2+3x+4x+12)+1
=[x.(x+1)+2.(x+1)][x.(x+3)+4.(x+3)]+1
=(x+1)(x+2)(x+3)(x+4)+1
=[(x+1)(x+4)][(x+2)(x+3)]+1
=(x2+5x+4)(x2+5x+6)+1
=(x2+5x+4)[(x2+5x+4)+2]+1
=(x2+5x+4)2+2(x2+5x+4)+1
=(x2+5x+4+1)2
=(x2+5x+5)2
(x^2+3x+2)(x^2+7x+12)+1
=(x2+x+2x+2)(x2+3x+4x+12)+1
=[x.(x+1)+2.(x+1)][x.(x+3)+4.(x+3)]+1
=(x+1)(x+2)(x+3)(x+4)+1
=[(x+1)(x+4)][(x+2)(x+3)]+1
=(x2+5x+4)(x2+5x+6)+1
=(x2+5x+4)[(x2+5x+4)+2]+1
=(x2+5x+4)2+2(x2+5x+4)+1
=(x2+5x+4+1)2
=(x2+5x+5)2
Phân tích đa thức thành nhân tử:
(x^2+3x+2)(x^2+7x+12)+1
Phân tích đa thức thành nhân tử:
(x^2+3x+2)(x^2+7x+12)+1
phân tích đa thức thành nhân tử:(x2+3x+2)(x2+7x+12)+1
Phân tích đa thức thành nhân tử:
(x^2+3x+2)(x^2+7x+12)
Phân tích đa thức thành nhân tử:
(x^2+3x+2)(x^2+7x+12)-24
Phân tích đa thức sau thành nhân tử:
(x^2+3x+2)(x^2+7x + 12)+x^2+5x-6
Phân tích các đa thức sau thành nhân tử
a) ( x - 1 ) ( x + 2 ) ( x + 3 ) ( x + 4 ) - 20
b) ( x2 + 3x + 2 ) ( x2 + 7x + 12 ) - 24
Phân tích đa thức thành nhân tử:
a) (x-1)(x-2)(x-3)(x-4)+1
b) (x2+3x+2)(x2+7x+12)+1
c) 12x2-3xy-8xz+2yz